Genetic and environmental risks for specific language impairment in children. - Bishop, D (2001)
Specific language impairment (SLI) is the term used to refer to unexplained difficulties in language acquisition in children. Over the past decade, there has been rapid growth of evidence indicating that genes play an important part in the aetiology of SLI. However, further progress in elucidating the role of genes in causing SLI is limited by our lack of understanding of the phenotype. Studies to date have been hampered by the fact that we do not know whether SLI should be treated as a discrete disorder or a continuous variable, let alone which measures should be used to identify cases, or how many subtypes there are. Recent research suggests that theoretically motivated measures of underlying processes may be better than conventional clinical diagnoses for identifying aetiologically distinct types of language impairment. There has been a tendency for researchers to embrace parsimony and look for a single cause of SLI-or in any event, to identify different subtypes, each with a different single cause. Research is reviewed that suggests that may not be a fruitful approach to SLI, and that an approach in terms of multiple risk and protective factors, which is widely adopted in medicine, is more realistic.